Corrigendum to "Faster algorithms for computing Hong's bound on absolute positiveness" [J. Symb. Comput. 45 (2010) 677–683]. (July 2018) - Koprowski, Przemysław; Mehlhorn, Kurt; Ray, Saurabh
Abstract: We show that a linear-time algorithm for computing Hong's bound for positive roots of a univariate polynomial, described by K. Mehlhorn and S. Ray in an article "Faster algorithms for computing Hong's bound on absolute positiveness", is incorrect. We present a corrected version.